Correlative Survey of Blended LiCoO2 and LiMn2O4 Cathode Materials for Lithium-ion Batteries - Okonkwo, Fidelis; Okonkwo, Chika (Computational And Experimental Research In Materials And Renewable Energy, 2024)
We employed the lithium-ion battery model in Multiphysics to simulate the electrochemical characteristics of lithium-ion batteries. These batteries consist of a cathode mixture comprising LiCoO2 and LiMn2O4, as well as quasi-graphite anode. Our simulations successfully replicated the discharge profiles of both unblended and blended cathodes across different current rates, aligning with results obtained from experiments. The energy and power densities of the blended cathode framework were regulated by adjusting the mix ratio in the simulation model. Additionally, the blended electrodes of LiCoO2 and LiMn2O4 demonstrated an above-average electrochemical performance, combining the characteristics of the two active materials.Keywords: Lithium-ion Battery; Blended Cathode Active Materials; Simulation; Experiment